Radiofrequency ablation of non-resectable lung tumors - Simanek, Vaclav; Klecka, Jiri; Treska, Vladislav; Ohlidalova, Kristyna; Mirka, Hynek (Biomedical papers, 2014)
Background: Radiofrequency thermal ablation (RFA) is a minimally invasive, image guided technique for destroying tumour cells without damage to adjacent healthy tissue. It is used for partial or complete ablation of non resectable lung cancers and cancers of metastases to lung, providing an effective, relatively safe option for patients ineligible for surgery. We describe our experience with it.Methods: In 2005 and 2006, we performed radiofrequency ablation of 7 lung lesions in 6 patients. RFA was done percutaneously under image guided CT scan in 5 patients and in one patient during thoracotomy when we found a radically unresectable tumor necessitating debulking. CT lung screening was performed after 6 months and PET/CT was done within 12 months.Results: In the course of the screening, we diagnosed regression in 2 patients, a stationary state in 2 cases and local tumor progression in 2 patients, using computed tomography within 6 months after RFA. Using PET/CT within 12 months, we diagnosed non-ablation and liver metastases (there were none before) in one of the two patients with a stationary state diagnosed by means of CT before and recurrence of primary tumor in another patient. In one case of diagnosed regression, we diagnosed tumor progression. The patients survived an average of 30 months (range 9 to 60 months).Conclusion: RFA of lung tumors is an easy method with little patient discomfort. It can be performed percutaneously using guided CT under general anaesthesia. RFA of lung tumors possibly alone or in combination with oncology treatment can prolong patient life.
Keywords: radiofrequency ablation; selective lung ventilation; lung CT scan; lung PET/CT